2011
DOI: 10.1002/ajmg.a.34371
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the clinical manifestations and survival of Korean patients with mucopolysaccharidosis type II: Emphasis on the cardiovascular complication and mortality cases

Abstract: Hunter syndrome (mucopolysaccharidosis II, MPS II) is a rare, X-linked disorder of glycosaminoglycan (GAG) catabolism caused by a deficiency in the activity of the lysosomal enzyme, iduronate-2-sulfatase (I2S). In this study, the medical records of 75 Korean patients with Hunter syndrome (74 males, 1 female) were retrospectively reviewed to investigate the frequency of organ involvement and survival at a single center. The three most common symptoms of organ involvement were hepatosplenomegaly (99%), facial dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 19 publications
5
28
0
Order By: Relevance
“…Similar to ours, several studies from different countries showed that the diagnosis was established on average 2-3 years after the onset of symptoms (20,(25)(26)(27)(28)(29). In a case of MPS, since patients exhibit different organ/system manifestations, they present to physicians from different branches including pediatricians, geneticists, cardiologists, ophthalmologists, orthopedists, and neurosurgery, and are diagnosed with different disorders such as primary valvular heart disease, Perthes disease, congenital talipes equinovarus, spondyloepiphyseal dysplasia, cataract, rheumatoid arthritis, craniosynostosis, pseudoachondroplasia, and inguinal hernia (23,27,29,30).…”
Section: Discussionsupporting
confidence: 86%
“…Similar to ours, several studies from different countries showed that the diagnosis was established on average 2-3 years after the onset of symptoms (20,(25)(26)(27)(28)(29). In a case of MPS, since patients exhibit different organ/system manifestations, they present to physicians from different branches including pediatricians, geneticists, cardiologists, ophthalmologists, orthopedists, and neurosurgery, and are diagnosed with different disorders such as primary valvular heart disease, Perthes disease, congenital talipes equinovarus, spondyloepiphyseal dysplasia, cataract, rheumatoid arthritis, craniosynostosis, pseudoachondroplasia, and inguinal hernia (23,27,29,30).…”
Section: Discussionsupporting
confidence: 86%
“…Cardiovascular complications, especially congestive heart failure, valvular thickening and dysfunction, and coronary artery occlusion continue to occur in stably treated patients, often resulting in death [5,11,17]. Development of validated, predictive biomarkers to identify individuals at-risk for severe cardiovascular disease is imperative to guide medical decision-making for clinicians and patients alike, and eventually to measure the efficacy of novel therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…While HSCT appears to attenuate coronary artery disease in severe MPS I [9,10], the ability of ERT to treat coronary disease is more questionable. Sudden and unexpected death, with evidence for coronary artery stenosis or myocardial infarction, has been reported in patients with both MPS I and II after 1–2 years of ERT [5,11]. …”
Section: Introductionmentioning
confidence: 99%
“…The true incidence of this finding is unknown since the cause of death in many adults with MPS, including those receiving ERT, is not usually closely investigated. Myocardial infarction has been reported as a cause of death in treatment-naïve adults with MPS IV38 and within 2 years of beginning ERT in adults with MPS I and II 39 40. Coronary artery bypass surgery has been performed in a 55-year-old treatment-naïve man with Scheie syndrome 41.…”
Section: Cardiac Expression Of Mpsmentioning
confidence: 99%